Co-feeding in Senegalese sole larvae with inert diet from mouth opening promotes growth at weaning - Engrola, S. (2014)
The aim of this study was to determine if sole larvae co-fed with inert diet at mouth opening would perform better than larvae fed with live prey and if such a feeding regime would produce better quality juveniles. The experiment was separated in to two phases: pelagic and benthic. In the pelagic phase, treatments consisted of the standard feeding regime (rotifer and Artemia feeding), the standard feeding regime and inert diet, and rotifer for a longer period than the standard feeding regime until larvae reached 9 days after hatching (DAH). By the end of the pelagic phase, when the postlarvae were 20 DAH, sole that were co-fed with inert diet from mouth opening, were significantly smaller in weight than postlarvae fed exclusively with live prey. Sole digestive maturation was improved by co-feeding the inert diet. Survival rates, skeletal deformities and quality evaluation were not affected by the feeding regimes. In the benthic phase, the postlarvae from standard feeding regime (pelagic phase) were separated in to two treatments: standard live Artemia metanauplii until weaning and standard frozen Artemia metanauplii until weaning. Remaining treatments were the follow up of treatments from the pelagic phase. At the end of the experiment i.e. 68 DAH, the postlarvae co-fed with inert diet from mouth opening were significantly larger than all the postlarvae from remaining feeding regimes. The results of the present study demonstrate that it is possible to offer inert diet to sole at mouth opening in a co-feeding regime and to produce better quality postlarvae. Co-fed sole were larger and had a better tail condition at the end of the weaning.